Pembangunan Fasilitas Peningkatan Sumber Daya Manusia di Kelurahan Makbon - Sonny Rumalutur; Suriano Buyung; Erna Kurniawati; , Marcelino Petrus Saptono; Stefany Margareta Martono; Luluk Suryani (Jurnal Kabar Masyarakat, 2024)
Makbon sub district is a sub district located in Makbon District, Sorong District, Southwest Papua Province. The Topographical conditions of the villages in Makbon District are mostly located in coastal areas with a total of 15 villages/sub districts. Public facilities are facilities provided for the public interest in the sense of facilities that are used for the benefit of all society in carrying out and making it easier for society to carry out their daily activities. Increasing development in villages is really needed by the community, especially to stimulate economic activities. One of the contributions of the Saint Paul Sorong Polytechnic in Papua, especially in Sorong, is providing community service. There are several things that the lecturer team can do to help the community, namely making sub district boundary moments, making street signs and making street lights for the community service in Makbon to develop facilities and human resources (HR) for the quality of life of the people in Makbon district, Sorong regency, Southwest Papua Province.